Snake envenomation in a north Indian hospital. Issue 2 (20th January 2005) - Sharma, N; Chauhan, S; Faruqi, S; Bhat, P; Varma, S
Abstract : Objectives: To study the clinical profile of snake envenomation in a tertiary referral north Indian hospital. Methods: Retrospective case note analysis of all cases of snakebite admitted to the medical emergency from January 1997 to December 2001. Results: Of a total of 142 cases of snakebite there were 86 elapid bites presenting with neuroparalytic symptoms and 52 viper bites having haemostatic abnormalities. Some 60.6% of the cases of snakebite occurred when the patient was asleep. Urban to rural ratio was 1:4.7 and male to female ratio was 4.25:1. Median time to arrival at our hospital after the bite was nine hours and mean duration of hospital stay was eight days. Twenty seven cases had acute renal failure and 75% of all elapid bites required assisted ventilation. Seventeen of 119 patients who received antivenom had an adverse event. The average dose of antivenom was 51.2 vials for elapid bites and 31 vials for viper bites. Overall mortality rate was 3.5%. Conclusion: Snakebites are common in the rural population of developing countries. There is a need to educate the public about the hazards of snakebite, early hospital referral, and treatment.